CONDITIONS OF FORMATION, PURIFICATION, AND CHARACTERIZATION OF AN ALPHA-GALACTOSIDASE OF TRICHODERMA-REESEI RUT C-30 - ZEILINGER, S; KRISTUFEK, D; ARISANATAC, I; HODITS, R; KUBICEK, CP (AMER SOC MICROBIOLOGY, 1993)
Trichoderma reesei RUT C-30 formed an extracellular alpha-galactosidase when it was grown in a batch culture containing lactose or locust bean gum as a carbon source. Short-chain alpha-galactosides (melibiose, raffinose, stachyose), as well as the monosaccharides galactose, dulcitol, arabinose, and arabitol, also induced alpha-galactosidase activity both when they were used as carbon sources (at a concentration of 1%) in batch cultures and in resting mycelia (at concentrations in the millimolar range). The addition of 50 mM glucose did not affect the induction of alpha-galactosidase formation by galactose. Alpha-Galactosidase from T. reesei RUT C-30 was purified to homogeneity from culture fluids of galactose-induced mycelia. The active enzyme was a 50 +/- 3-kDa, nonglycosylated monomer which had an isoelectric point of 5.2. It was active against several alpha-galactosides (p-nitrophenyl-alpha-D-galactoside, melibiose, raffinose, and stachyose) and galactomannan (locust bean gum) and was inhibited by the product galactose. It released galactose from locust bean gum and exhibited synergism with T. reesei beta-mannanase. Its activity was optimal at pH 4, and it displayed broad pH stability (pH 4 to 8). Its temperature stability was moderate (60 min at 50-degrees-C resulted in recovery of 70% of activity), and its highest level of activity occurred at 60-degrees-C. Its action on galactomannan was increased by the presence of beta-mannanase.
Keywords: DEGRADING ENZYMES; HYDROLYSIS; MANNANASE; CELLULASE; INDUCTION; QM-9414; Biotechnology & Applied Microbiology; Microbiology